2017
DOI: 10.1093/ndt/gfx066
|View full text |Cite
|
Sign up to set email alerts
|

A novel homozygous UMOD mutation reveals gene dosage effects on uromodulin processing and urinary excretion

Abstract: Heterozygous mutations in UMOD encoding the urinary protein uromodulin are the most common genetic cause of autosomal dominant tubulointerstitial kidney disease (ADTKD). We describe the exceptional case of a patient from a consanguineous family carrying a novel homozygous UMOD mutation (p.C120Y) affecting a conserved cysteine residue within the EGF-like domain III of uromodulin. Comparison of heterozygote and homozygote mutation carriers revealed a gene dosage effect with unprecedented low levels of uromodulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 27 publications
0
18
0
3
Order By: Relevance
“…Despite the seven decades of work on Tamm-Horsfall protein, neither the cellular target nor the downstream effectors of UMOD action have been definitively identified. Biologic targeting using UMOD itself as a therapeutic would be complicated by its large size and requirement of proper folding and maintenance of 24 cysteine-cysteine disulfide bonds (50). Similar experiences complicate targeting genetic variants associated with type 2 diabetes mellitus and Alzheimer disease GWAS in which TCF7L2 (51,52) and ApoE4 (53) polymorphisms respectively strongly associate, yet the biologic mechanisms underlying their genetic association with disease remains frustratingly obscure.…”
Section: Mendelian Diseasementioning
confidence: 99%
“…Despite the seven decades of work on Tamm-Horsfall protein, neither the cellular target nor the downstream effectors of UMOD action have been definitively identified. Biologic targeting using UMOD itself as a therapeutic would be complicated by its large size and requirement of proper folding and maintenance of 24 cysteine-cysteine disulfide bonds (50). Similar experiences complicate targeting genetic variants associated with type 2 diabetes mellitus and Alzheimer disease GWAS in which TCF7L2 (51,52) and ApoE4 (53) polymorphisms respectively strongly associate, yet the biologic mechanisms underlying their genetic association with disease remains frustratingly obscure.…”
Section: Mendelian Diseasementioning
confidence: 99%
“…Its expression is regulated by transcription factors such as SP1, TP3, POU2F1, STAT3 and RARA [ 105 ]. Researchers found that more than 90% of UMOD gene mutations occurred in exons 3 and 4 [ 27 ]. This mutation causes autosomal dominant tubulointerstitial kidney disease (ADTKD-UMOD), also known as familial juvenile HUA nephropathy (FJHN) [ 27 , 106 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers found that more than 90% of UMOD gene mutations occurred in exons 3 and 4 [ 27 ]. This mutation causes autosomal dominant tubulointerstitial kidney disease (ADTKD-UMOD), also known as familial juvenile HUA nephropathy (FJHN) [ 27 , 106 ]. This disease is an autosomal dominant disease, which is rare in children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a glycoprotein that is expressed in the thick ascending limb (TAL) of the Loop of Henle and was first purified by Igor Tamm and Frank Horsfall in 1952 [1315]. Mutations in the UMOD gene are associated with medullary cystic kidney disease and autosomal dominant tubulointerstitial kidney disease [16, 17]. In healthy kidneys, UMOD is thought to have a role in salt transport in the tubules, innate immunity and protection against kidney stones [18].…”
Section: Introductionmentioning
confidence: 99%